Secessionism and the European Union : the future of Flanders, Scotland, and Catalonia - Duerr, Glen M. E. (Lexington Books, 2015)
"This study examines three different cases - Flanders in Belgium, Scotland in the UK, and Catalonia in Spain - to investigate how secessionist political parties are approaching the issues of independence. All of these cases are different with respect to history, governmental structure, and economic situation. Yet all of the cases are similar in some ways - they are close to the same size (in terms of population), operate withing mature democratic political systems, have distinct secessionist political parties, and all reside within member states of the EU. Categorically, in all cases there are also shared influences of ability of the region to secede: insitituitons, interests, and ideas"--Back cover.